Caught Between Scylla and Charybdis: The Uncertain Role of the Humanities at the Costa Rica Institute of Technology: Pág. 67 - 85 - Castillo-Rodríguez, Larissa (2025)
The presence of humanities within the Costa Rica Institute of Technology (ITCR) is analyzed in this article. Moreover, the fundamental characteristics of the integration of humanistic knowledge in the context of this higher education public institution are presented. In that way, the model of humanities integration in the development of a university which focuses on techno-scientific knowledge can be critically analyzed. The authors hypothesize that both teaching and research in the disciplinary field of humanities are placed in an ambivalent position within the university structure of ITCR, which ranges from forced presence due to accreditation processes, to a placement as non-essential disciplines in institutional tasks as well. Futhermore, this research is a bibliographic study based on the review of both primary and secondary sources such as texts and academic journals, in order to reflect in a critical way on the concepts proposed in them.